Potraumatyczny wzrost - zróżnicowanie ze względu na rodzaj doświadczonego zdarzenia - Ogińska-Bulik, Nina (Acta Universitatis Lodziensis. Folia Psychologica, 2013)
The experience of negative life events may involve such negative as positive effects. These positive, referred to as posttraumatic growth, include changes in self-perception, relations to others, and changes in philosophy of life. Among the factors that determine the occurrence of positive changes after trauma the type of experienced event and socio-demographic variables are mentioned. The aim of the study was to determine the relationship between the type of experienced negative event, gender, age and severity of posttraumatic growth. The study group consists of 730 participants (49,6% men, 50,4% – women), aged 16–75 years (M = 36,5, SD = 14,3), who experienced various negative life events. Polish version of Posttraumatic Growth Inventory was used in the study. The results indicated that type of experienced event and gender were related to the level of posttraumatic growth. Moreover the results indicated that examining the relationship between socio-demographic variables and posttraumatic growth should take into account not only the overall result but also the different areas of growth.